Performance of Low-Cost GNSS in Structural Health Monitoring Studies: Shake Table Tests - Topal, G. Oku; Akpinar, B.; Karabulut, M. F.; Aykut, N. O.; Yiğit, Cemal Özer; Dindar, A. A.; Doran, B. (Springer, 2024)
This contribution presents an evaluation of the effectiveness of the low-cost GNSS technique in structural health monitoring and GNSS-seismology applications. To evaluate the ability of the low-cost GNSS technique, harmonic oscillation, and earthquake tests were carried out employing the ZED-F9P-02B OEM low-cost GNSS receiver and two low-cost antennas (A10 and ANN-MB U-Blox) on a single-axis shake table. Harmonic motion experiments include frequencies ranging from 0.35 to 5.80 Hz and amplitudes between 10 and 25 mm. Moreover, the Loma-Prieta and Kobe earthquakes were simulated using a shake table to evaluate the ability of the low-cost GNSS technique to detect earthquake-induced strong ground motions. GNSS observations collected at a 20 Hz sampling interval were processed using the CSRS-PPP online service, and the ability of the low-cost GNSS technique to detect horizontal directional dynamic behaviors was validated using the relative positioning and Linear Variable Differential Transformer (LVDT) data as a reference both time and frequency domain. The max. RMSE values obtained according to the 15 harmonic oscillation test results are 2.8 mm for Geodetic Antenna Relative results, 3.3 mm for PPP, 3.2 mm for A10 Relative, 3.3 mm for PPP, 3.3 mm for UBX Antenna Relative, and 3.7 mm for PPP Results. According to the earthquake test results, the max. RMSE values obtained are 2.6 mm for Geodetic Antenna Relative results, 3.4 mm for PPP, 2.4 mm for A10 Relative, 3.8 mm for A10 PPP, 2.9 mm for UBX Antenna Relative and 4.2 mm for PPP. All results have shown that the ZED-F9P-02B GNSS receiver efficiently detects natural frequencies and structural behaviors.
Keywords: Low-cost GNSS; Shake Table; Relative GNSS; GNSS-PPP